National reports on small and microbusiness in the Caribbean : a summary of National consultations for the Caribbean Enterprise Education and Development (CEED) Trust : draft - OAS ([s.n.] [S.l.], 1996)
Presents national reports which focus on aspects such as the legal framework; the institutional framework; financing; education and skills training; and, regional institutions. Suggests projects and activities.